Simultaneously improved electromagnetic interference shielding and mechanical performance of segregated carbon nanotube/polypropylene composite via solid phase molding. (1st March 2018) - Wu, Hong-Yuan; Jia, Li-Chuan; Yan, Ding-Xiang; Gao, Jie-feng; Zhang, Xiao-Peng; Ren, Peng-Gang; Li, Zhong-Ming
Abstract: Conductive polymer composite with segregated structure has been well demonstrated to achieve high electromagnetic interference shielding effectiveness (EMI SE) due to the selectively distributed electrical nanofillers to establish desirable conductive networks. Nevertheless, the formation of segregated structure in low-melt-viscosity semi-crystalline polymer is still challenged and the segregated composite always suffers poor mechanical performance. Herein, elevated pressure and temperature were utilized to make a typical semi-crystalline polymer, polypropylene (PP), hold solid phase to restrict the diffusion of carbon nanotube (CNT) into its interior. Segregated CNT networks were facilely constructed in the resultant CNT/PP composite and imparted it with a superior EMI SE of 48.3 dB at 2.2 mm thickness and 5.0 wt% CNT loading, the highest EMI shielding level among the reported CNT/polymer composites at equivalent material thickness and CNT loading. Moreover, the elevated pressure and temperature effect dramatically increase the compressive, tensile, and flexural strength (modulus) of the CNT/PP composite by 133% (65%), 74% (130%) and 53% (50%), respectively, in comparison to those for conventional segregated CNT/PP composite, really overcoming the major mechanical shortcoming in the development of segregated composites for EMI shielding. Our work provides a facile strategy to fabricate the efficient EMI shielding and robust material with the construction of typical segregated structure in low-melt-viscosity semi-crystalline polymers.